Proactive not punitive: Approaching academic integrity from an educational perspective - Liang, Ann; Maddison, Tasha (Canadian Perspectives on Academic Integrity, 2021)
Our implementation of Turnitin Similarity Software at Saskatchewan Polytechnic strengthened the overall support services for both faculty and students in preventing plagiarism. Using a holistic approach we drew on the collective intelligence of experts from several departments, which resulted in training sessions, curriculum design support and intensive student support. Our research used a variety of methods such as a literature review, quantitative data from user surveys, results from the similarity software and qualitative data from focus groups that center on perceptions of the issue within the program and the perceived benefits of the software. Highlights include the use of Turnitin as a writing improvement tool for students, shifting the mindset of faculty from being punitive to being proactive, writing clear and consistent assignment instructions, embedding student supports, mandatory student and faculty training in Turnitin, academic integrity education, as well as protecting student rights and intellectual freedom.